As propriedades do verbo e a inversão - Mikołajczak, Sylwia (Studia Romanica Posnaniensia, 2004)
The article aims to present basic verb properties engaged in the process of inversion. In Portuguese, that is a language with a null-subject parameter, the inversion seems to be more related to the proper verb rather than subject characteristics. We differentiate semantic features of a verb which categorise the verbs expressing movement, 'entry in the scene', and psychological ones as the classes of verbs prompted to inversion. The semantic features of the differentiated categories relate to syntactic inversion favouring intransitive and inaccusative verbs. Last but not least, the information and communicative factors place the verbs in the sentence initial position, opposite to the subject rhematic elements.